2015
DOI: 10.1007/s00259-015-3022-9
|View full text |Cite
|
Sign up to set email alerts
|

Persistent quality of life impairments in differentiated thyroid cancer patients: results from a monitoring programme

Abstract: PurposeHealth-related quality of life (HRQOL) in differentiated thyroid cancer (DTC) research has so far received little attention and available results are conflicting. We studied the HRQOL of radioiodine-naive DTC patients in comparison with the general population (GP), investigated the course of HRQOL up to 30 months after radioiodine remnant ablation (RAA) and sought to identify patient characteristics associated with HRQOL.MethodsWe analysed data from routine HRQOL monitoring at a nuclear medicine departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 35 publications
6
48
0
3
Order By: Relevance
“…HRQoL was higher at the one-year follow-up, which was expected due to the timing of the first questionnaire. Similar results, with an increasing HRQoL during the first year have been demonstrated in previous studies 47,171 . The higher HRQoL after one year was probably related to a real improvement, but could be affected by a response shift.…”
Section: Hrqol In Thyroid Cancer Patients During Follow-upsupporting
confidence: 91%
See 2 more Smart Citations
“…HRQoL was higher at the one-year follow-up, which was expected due to the timing of the first questionnaire. Similar results, with an increasing HRQoL during the first year have been demonstrated in previous studies 47,171 . The higher HRQoL after one year was probably related to a real improvement, but could be affected by a response shift.…”
Section: Hrqol In Thyroid Cancer Patients During Follow-upsupporting
confidence: 91%
“…A few studies assess HRQoL longitudinally. Although HRQoL increases over time, it does not reach the same levels as a general population 171 . During the first years of follow-up, HRQoL seems to fluctuate and starts increasing after five years 178 .…”
Section: Hrqol In Thyroid Cancer Survivorsmentioning
confidence: 80%
See 1 more Smart Citation
“…A cancer diagnosis may have profound effects on the lives of adolescents and young adults, interfering with the attainment of normal developmental milestones. [6][7][8][9] A systematic review on HR-QOL among thyroid cancer survivors showed mixed results; thyroid cancer survivors, in general, have either a similar or a worse HR-QOL compared with the normative sample, and survivors reported specific medical problems that were associated with poorer HR-QOL. 5 In general, the diagnosis, treatment, and long-term follow-up of thyroid cancer can result in a decreased HR-QOL and increase in disease-specific symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…5 In general, the diagnosis, treatment, and long-term follow-up of thyroid cancer can result in a decreased HR-QOL and increase in disease-specific symptoms. [6][7][8][9] A systematic review on HR-QOL among thyroid cancer survivors showed mixed results; thyroid cancer survivors, in general, have either a similar or a worse HR-QOL compared with the normative sample, and survivors reported specific medical problems that were associated with poorer HR-QOL. 6 However, little is known about age-related differences in HR-QOL.…”
Section: Introductionmentioning
confidence: 99%